2010
DOI: 10.1002/art.27325
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1 gene cluster variants with innate cytokine production profiles and osteoarthritis in subjects from the Genetics, Osteoarthritis and Progression Study

Abstract: Objective. To assess whether genetic variation in the interleukin-1 (IL-1) gene cluster contributes to familial osteoarthritis (OA) by influencing innate ex vivo production of IL-1␤ or IL-1 receptor antagonist (IL-1Ra).Methods. Innate ex vivo IL-1␤ and IL-1Ra production upon lipopolysaccharide (LPS) stimulation of whole blood cells was measured in subjects from the Genetics, Osteoarthritis and Progression (GARP) Study, which includes sibling pairs in which at least one sibling has symptomatic OA at multiple si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(51 reference statements)
0
7
0
1
Order By: Relevance
“…The composite genotype of the two was therefore uncommon and uninformative in Asians . In addition, contradicting findings have been reported regarding the association between these IL‐1 markers and periodontitis or between these markers and the production of IL‐1 proteins ; although in some studies, the small sample size might have contributed to negative or inconclusive findings. The IL‐1 functional patterns used in this study were found commonly in all the populations studied, and as expected, the carriage rate differed among the ethnic groups, with for example 72% of African Americans testing positive compared to 27% of Caucasians and 11% of Asians.…”
Section: Discussionmentioning
confidence: 95%
“…The composite genotype of the two was therefore uncommon and uninformative in Asians . In addition, contradicting findings have been reported regarding the association between these IL‐1 markers and periodontitis or between these markers and the production of IL‐1 proteins ; although in some studies, the small sample size might have contributed to negative or inconclusive findings. The IL‐1 functional patterns used in this study were found commonly in all the populations studied, and as expected, the carriage rate differed among the ethnic groups, with for example 72% of African Americans testing positive compared to 27% of Caucasians and 11% of Asians.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence of genetic/familial risk factors was reported (2936). Some studies reported associations between elevated body mass index and other measures of body mass and multiple joint OA(22, 37, 38), but this finding was not consistent(39, 40).…”
Section: Resultsmentioning
confidence: 99%
“…These included summed radiographic grades(44, 50) and sums of numbers of affected joints or joint groups(30, 36, 45, 5153). Cerhan, et al, reported associations between the number of joints with OA, number of joint groups with OA, and a binary definition of GOA (3 or more joints with K–L grade of 2 or higher) and survival time(51).…”
Section: Resultsmentioning
confidence: 99%
“…The primary objective of this study was to test whether IL1RN gene variations previously associated cross-sectionally with knee OA severity 15,16,38 or susceptibility 39,40 might be associated with longitudinally monitored radiographic progression of knee OA in a population cohort. We found a significant association between progression and several SNPs and their haplotypes in the gene for IL-1Ra, indicating that variants of this gene may be important predictive markers of severity or progression.…”
Section: Discussionmentioning
confidence: 99%